Sisters in structure but different in character, some benzaldehyde and cinnamaldehyde derivatives differentially tune Aspergillus flavus secondary metabolism - Bisceglie, Franco (Sci Rep, 2020)
Great are the expectations for a new generation of antimicrobials, and strenuous are the research efforts towards the exploration of diverse molecular scaffolds—possibly of natural origin – aimed at the synthesis of new compounds against the spread of hazardous fungi. Also high but winding are the paths leading to the definition of biological targets specifically fitting the drug’s structural characteristics. The present study is addressed to inspect differential biological behaviours of cinnamaldehyde and benzaldehyde thiosemicarbazone scaffolds, exploiting the secondary metabolism of the mycotoxigenic phytopathogen Aspergillus flavus. Interestingly, owing to modifications on the parent chemical scaffold, some thiosemicarbazones displayed an increased specificity against one or more developmental processes (conidia germination, aflatoxin biosynthesis, sclerotia production) of A. flavus biology. Through the comparative analysis of results, the ligand-based screening strategy here described has allowed us to delineate which modifications are more promising for distinct purposes: from the control of mycotoxins contamination in food and feed commodities, to the environmental management of microbial pathogens, to the investigation of specific structure–activity features for new generation drug discovery.